STRATEGI MEDIA RELATIONS PDAM SURAKARTA DALAM UPAYA MEMPERTAHANKAN CITRA PERUSAHAAN - Rahmawati, Rahmawati; Pratiwi, Rhesa Zuhriya (LENTERA, 2019)
One of the functions of media relation for a company is to craft good image and reputation of the company in the public’s eye. Related to such function, the aim of this research is to explain the function of the media relation of the PDAM Surakarta to maintain the good image of the company. This research apllies descriptive-qualitative technique of analysis and collects data through observations, indepth interviews, and documentations. Findings of this research are: (1) PDAM Surakarta manages both internal and external relations by using media to provide informations about the company; (2) creating media relations through press release, media visits, and press tour, and (3) expanding its’ networks by cooperating with mass media such as Solopos, RRI, RIA RM, TA TV, and Metta FM.Keywords: Company image, media relations, PDAM Surakarta